Hidden treasures of the sea. - National Geographic Society (U.S.). (Washington, D.C. National Geographic Society, 1988)
An introduction to nautical archeology, focusing on social,cultural, and political history as exposed by shipwrecks from ancient times to the present.
Keywords: Treasure troves -- Juvenile literature; Shipwrecks -- Juvenile literature; Underwater archaeology -- Juvenile literature; Archaeology -- Juvenile literature